2014
DOI: 10.1186/1471-2164-15-811
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of genome-wide gene expression and DNA methylation in abnormal cloned piglets

Abstract: BackgroundEpigenetic modifications (especially altered DNA methylation) resulting in altered gene expression may be one reason for development failure or abnormalities in cloned animals, but the underlying mechanism of the abnormal phenotype in cloned piglets remains unknown. Some cloned piglets in our study showed abnormal phenotypes such as large tongue (longer and thicker), weak muscles, and exomphalos. Here we conducted DNA methylation (DNAm) immunoprecipitation and high throughput sequencing (MeDIP-seq) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(63 citation statements)
references
References 82 publications
(90 reference statements)
3
59
1
Order By: Relevance
“…As remarked by other authors, nature allows a certain amount of flexibility in the epigenome and gene expression during growth and development (28). As might be anticipated, clones that fail during gestation and/or have physiological abnormalities have been found to have abnormal epigenetic patterns whereas those that thrive have a comparatively normal pattern (28,36). It is also interesting to note that the gestational losses and abnormalities observed in SCNT were also noted during the development of in vitro embryo production and culture techniques in domestic species in the 1990s.…”
Section: Setting the Stage-historical And Evolutionary Perspectivementioning
confidence: 65%
See 1 more Smart Citation
“…As remarked by other authors, nature allows a certain amount of flexibility in the epigenome and gene expression during growth and development (28). As might be anticipated, clones that fail during gestation and/or have physiological abnormalities have been found to have abnormal epigenetic patterns whereas those that thrive have a comparatively normal pattern (28,36). It is also interesting to note that the gestational losses and abnormalities observed in SCNT were also noted during the development of in vitro embryo production and culture techniques in domestic species in the 1990s.…”
Section: Setting the Stage-historical And Evolutionary Perspectivementioning
confidence: 65%
“…Due to the cost and extended generation times for domestic species, most of these studies, so far, have focused on early embryonic and fetal development. As with epigenetic patterns described above, many of these studies report either the normal expression of key genes after a reconstructed embryo passes a developmental checkpoint (e.g., blastocyst formation) or abnormal gene expression after failure to pass such checkpoints (28,36). These experiments focused mainly on how SCNT worked or did not work, and few use SCNT to explore questions regarding developmental regulation of genes.…”
Section: Scnt and Transgenic Animal Productionmentioning
confidence: 99%
“…The raw sequence data were assessed and tags that contained adaptors, were of low quality, or showed more than 10 % unidentified nucleotides, were removed. Only clean reads were used for subsequent analysis, and the unique reads were used for identifying differentially expressed genes with log 2 ratio ≥1 and false discovery rate (FDR) ≤0.001 Li et al 2014). …”
Section: Rna Sequencing and Data Analysismentioning
confidence: 99%
“…; Li et al . ). Some studies also identified and functionally/biologically characterised differentially methylated genes (DMGs) or differentially expressed genes (DEGs) that may participate in muscle development of pigs and cattle (Huang et al .…”
Section: Introductionmentioning
confidence: 97%